S&G ORI: un sistema de información web para el seguimiento y la gestión de actividades por parte de la Oficina de Relaciones Internacionales (ORI) de la Universidad Antonio Nariño (2022)
The Office of International Relations (ORI) aims to promote the process of comprehensive internationalization of the Antonio Nariño University (UAN) and the collaboration of the university society in strategic activities that involve understanding of the dynamics, global trends and relationship with the world. This is developed with services provided to the university, which focus on a single objective: to improve academic and professional development in the university community inside and outside the country. At present, the ORI must carry out several administrative tasks in order to have the updated information of partner universities, conventions, and activities carried out within the framework of each convention, in addition to the reports submitted by the internationalization leaders on these activities. Currently, these tasks are done manually, so they are subject to human error and require more time than would be necessary if a software product were available for their automation. This undergraduate degree project addresses this problem and presents a solution through the development of a web application with which these tasks developed by the ORI team and its leaders can be automated.